2005
DOI: 10.1177/0363546505278301
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Treatment of Posterior Shoulder Instability

Abstract: Arthroscopic treatment of posterior shoulder instability is an effective means to improve symptoms associated with recurrent posterior subluxation of the shoulder. It can provide predictable success in the setting of unidirectional, nonvoluntary posterior instability without prior surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(73 citation statements)
references
References 45 publications
2
69
1
1
Order By: Relevance
“…Similarly, the retrospective level 4 investigation of 20 athletic shoulders by McIntyre et al [13] utilized an anchorless suture technique reported a high failure rate of 25% (5 of 20 shoulders). An additional level 4 report of 33 patients by Provencher et al [12] concluded that capsular plication rather than labral suture anchor repair had a higher chance of failure among their 7 reported failed cases (P = 0.10). Thus, arthroscopic posterior stabilization procedures utilizing suture anchors to address capsular pathology may provide the most consistent and favorable outcomes and return to sport [13,18,27,28] .…”
Section: Surgical Managementmentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, the retrospective level 4 investigation of 20 athletic shoulders by McIntyre et al [13] utilized an anchorless suture technique reported a high failure rate of 25% (5 of 20 shoulders). An additional level 4 report of 33 patients by Provencher et al [12] concluded that capsular plication rather than labral suture anchor repair had a higher chance of failure among their 7 reported failed cases (P = 0.10). Thus, arthroscopic posterior stabilization procedures utilizing suture anchors to address capsular pathology may provide the most consistent and favorable outcomes and return to sport [13,18,27,28] .…”
Section: Surgical Managementmentioning
confidence: 97%
“…In a case series of 33 patients, Provencher et al [12] demonstrated that patients with voluntary instability resulted in worse outcomes. Specifically, they identified recurrent instability to be specific to patients with a voluntary instability component, whereas, all patients with involuntary instability were stable at followup (P = 0.025).…”
Section: Diagnosis Of Instabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with magnetic resonance imaging (MRI), MRA can better define labral lesions and rotator interval lesions, as well as assess capsular volume. 28 MRA is currently the best method for imaging capsulolabral lesions. 36 Williams et al 42 recommend physical therapy as the primary treatment option for individuals with symptomatic posterior instability, with operative repair dependent on the extent of disability and desired level of activity.…”
Section: Imagingmentioning
confidence: 99%
“…The function subset (maximum score, 60) improved from a mean of 32 (range, 18-45) at the initial evaluation to a mean of 54 (range, 51-56) at discharge. At the initial physical therapy evaluation, the patients had a mean of 22 (range, 15-28) on the pain subset (maximum score, 30), and at discharge had a mean of 27 (range, [21][22][23][24][25][26][27][28][29]. The patients had a mean satisfaction subset (maximum score, 10) of 4 (range, 0-6) at the initial evaluation, 6 (range, 5-7) at discharge.…”
Section: 37mentioning
confidence: 99%